G272 Intensive care admissions in children with down syndrome: trends in incidence and outcome. (25th October 2020) - Rapaport, B; Marder, E; Smyth, AR; Parslow, RC; Vyas, H; Prayle, AP
Abstract : Purpose: In the first three years of life approximately 50% of children with Down Syndrome require hospitalisation. We aimed to investigate the epidemiology of admissions to Paediatric Intensive Care Units (PICU) in the UK for those with Down Syndrome, and to explore the impact of cardiac disease on admission. Methods: We obtained demographic and clinical data from PICANet, the UK national audit database, on all children admitted to PICU who had a recorded diagnosis Down Syndrome. Patients were categorised as either cardiac or non-cardiac depending on their primary admission diagnosis. We used data from the Down National Down Syndrome Cytogenetic Register to calculate the proportion of children born with Down Syndrome who were admitted to PICU. Results: Our dataset included 2791 patients with 4561 admissions to PICU. Most patients had one admission to PICU, although there was an increasing trend for readmissions. Overall PICU mortality was 4.7% in this cohort. Over the study period mortality did not significantly change. A quarter of children born with Down Syndrome were admitted to a PICU by the age of 17 months (95% CI 13 – 24 months). Half of the admissions were due to cardiac disease. Conclusions: These data will inform future planning of PICU services and counselling of parents of new-borns with Down Syndrome. If current trends continue, there will be increasing numbers of repeat admissions of children with Down Syndrome presenting with both cardiac and non-cardiac disease.